Effectiveness of different groups of preparations for pre-sowing treatment of winter wheat seeds - Halyna Slobodianyk; Ivan Zhilyak; Ivan Mostoviak; Serhii Shchetyna; Oleksandr Zabolotnyi (Наукові горизонти, 2022)
The first stage of modernizing cultivation of the main grain crops lies in the exogenous use of natural growth regulators and nanofertilisers for pre-sowing seed treatment. Special attention is paid to the quality of winter wheat seed material, given the high probability of seed germination in stressful climatic conditions and the need to form winter-hardy crops. Therewith, this study is relevant because modern requirements for agronomic biofortification of plant products make provision for the introduction of environmentally safe, effective, and cost-effective measures in the cultivation of agricultural crops. The use of preparations based on fulvic acids and growth regulators is an effective way to regulate the morphogenesis and productivity of winter wheat. The purpose of this paper was to investigate the effect of pre-sowing treatment of winter wheat seeds with such preparations as Fulvohumin (chelated fertiliser), 1-naphthyl-acetic acid (auxin) and succinic acid (biogenic growth stimulator, adaptogen) on germination and biometric parameters of seedlings. The study involved the use of laboratory and statistical methods. It was found that pre-sowing soaking in 1% Fulvohumin solution increased the energy of seed germination, seedlings contained a large proportion of dry matter, compared to seed treatment with 0.025% succinic acid solution or 1-naphthyl-acetic acid. In terms of germination energy and raw root mass of 7-day shoots, a combination of Fulvohumin and 1-naphthyl-acetic acid was effective. The largest total length and crude weight of 7-day seedlings were after joint seed treatment with Fulvohumin and succinic acid. According to the totality of seedling formation data, complex pre-sowing treatment of winter wheat seeds with Fulvohumin is recommended together with succinic acid and 1-naphthyl-acetic acid. Treatment exclusively with 1-naphthyl-acetic acid was ineffective. These studies are promising for programming field seed germination and mathematical modelling of winter crop growth at the initial stages of ontogenesis in the field